SEJARAH PERKEMBANGAN PARIWISATA DI KABUPATEN BINTAN KEPULAUAN RIAU TAHUN 1996-2019 - Muhammad Nur Bintang; Bedriati Ibrahim; Asyrul Fikri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The development of tourism is a very fast development sector, especially in Indonesia. One of the well-known tourism sectors is tourism in the resort and beach sector. In Indonesia, there is already a well-known tourism in Bintan. It started with the cooperation of three countries with the SIJORI agreement. The following applies: (1) To see the historical condition of tourism in Bintan in 1996. (2) For tourism development in Bintan from 1996 to 2019. (3) To find out about the cooperation between the Indonesian government and Singapore in the development of tourism. (4) To see the impact of the development of tourism on the economy and social for the community around the tourist attraction. In this study the author uses the historical method, namely by using the methods: (1) Heuristics. (2) Verification. (3) Interpretation. (4) Historiography. The history of tourism in Bintan starts from the existence of the SIJORI (Singapore - Johor - Riau) cooperation agreement which is for 1990. This agreement is an economic agreement between three mutually beneficial countries, called the Growth Triangle where in the agreement the three countries mutually take advantage of the respective advantages of each country, Singapore has capital and technology, Malaysia has a market and Indonesia has land and manpower. Development of tourism in Bintan is very advanced and also famous in Bintan is very popular among foreign and local tourists , so that due to the rapid development of tourism in Bintan, it certainly affects aspects such as social and economic aspects of the people around these tourist objects.Key Words: History of Tourism Development